Assessment of risk of variant creutzfeldt‐Jakob disease (vCJD) from use of bovine heparin. Issue 5 (5th March 2020) - Huang, Yin; Forshee, Richard A.; Keire, David; Lee, Sau; Gregori, Luisa; Asher, David M.; Bett, Cyrus; Niland, Brian; Brubaker, Scott A.; Anderson, Steven A.; Yang, Hong
Abstract: Purpose: In the late1990s, reacting to the outbreak of bovine spongiform encephalopathy (BSE) in the United Kingdom that caused a new variant of Creutzfeldt‐Jakob disease (vCJD) in humans, manufacturers withdrew bovine heparin from the market in the United States. There have been growing concerns about the adequate supply and safety of porcine heparin. Since the BSE epidemic has been declining markedly, the US Food and Drug Administration reevaluates the vCJD risk via use of bovine heparin. Methods: We developed a computational model to estimate the vCJD risk to patients receiving bovine heparin injections. The model incorporated information including BSE prevalence, infectivity levels in the intestines, manufacturing batch size, yield of heparin, reduction in infectivity by manufacturing process, and the dose‐response relationship. Results: The model estimates a median risk of vCJD infection from a single intravenous dose (10 000 USP units) of heparin made from US‐sourced bovine intestines to be 6.9 × 10 −9 (2.5‐97.fifth percentile: 1.5 × 10 −9 ‐4.3 × 10 −8 ), a risk of 1 in 145 million, and 4.6 × 10 −8 (2.5‐97.fifth percentile: 1.1 × 10 −8 ‐2.6 × 10 −7 ), a risk of 1 in 22 million for Canada‐sourced products. The model estimates a median risk of 1.4 × 10 −7 (2.5‐97.fifth percentile: 2.9 × 10 −8 ‐9.3 × 10 −7 ) and 9.6 × 10 −7 (2.5‐97.fifth percentile: 2.1 × 10 −7 ‐5.6 × 10 −6 ) for a typical treatment for venous thromboembolism (infusion of 2‐4 doses daily per week) using US‐sourced and Canada‐sourced bovine heparin, respectively. Conclusions: The model estimates the vCJD risk from use of heparin when appropriately manufactured from US or Canadian cattle is likely small. The model and conclusions should not be applied to other medicinal products manufactured using bovine‐derived materials.